2007
DOI: 10.1007/s00267-006-0228-4
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Framework for Multipollutant Air Quality Management and Its Application in Georgia

Abstract: Air protection agencies in the United States increasingly confront non-attainment of air quality standards for multiple pollutants sharing interrelated emission origins. Traditional approaches to attainment planning face important limitations that are magnified in the multipollutant context. Recognizing those limitations, the Georgia Environmental Protection Division has adopted an integrated framework to address ozone, fine particulate matter, and regional haze in the state. Rather than applying atmospheric m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…A collaborative approach, if practicable, would better reflect the fact that both state and federal measures are often needed to achieve attainment. The plans could also include integrated consideration of costs and benefits across multiple pollutants, as recommended by several studies (Chestnut et al, 2006;Cohan et al, 2007;National Research Council, 2004;Scheffe et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A collaborative approach, if practicable, would better reflect the fact that both state and federal measures are often needed to achieve attainment. The plans could also include integrated consideration of costs and benefits across multiple pollutants, as recommended by several studies (Chestnut et al, 2006;Cohan et al, 2007;National Research Council, 2004;Scheffe et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies have shown that cost and benefit quantification could in theory enhance the selection of control measures for attainment plans (Chestnut et al, 2006;Cohan et al, 2007). However, the extent to which actual SIPs have quantified costs and benefits has not previously been investigated systematically.…”
Section: Prevalence Of Cost and Health Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve AQ and mitigate the deleterious effects on human health, ecosystems, and climate, policy makers and scientists rely on comprehensive computer modeling systems that simulate emissions, transport, chemistry, and deposition of air pollutants to design emission control strategies for achieving healthy sustainable AQ [Cohan et al, 2007]. The combined meteorology and air quality modeling system WRF/CMAQ-composed of the National Center for Atmospheric Research Weather Research and Forecast (WRF) model [Skamarock et al, 2008] and the United States (U.S.) Environmental Protection Agency (EPA) Community Multiscale Air Quality (CMAQ) model [Byun and Schere, 2006] is an important decision support tool that is used to help understand the chemical and physical processes involved in AQ degradation and to develop policy to mitigate harmful effects of air pollution on human health and the environment around the world [Isakov et al, 2007;Wang et al, 2010;Compton et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…Effective attainment of ground-level O 3 concentration depends upon a reliable understanding of how O 3 responds to control of its precursors (Cohan et al, 2007). In this study, we apply the Comprehensive Air Quality Model with Extensions model (CAMx) to study the typical weather system and the exact formation mechanism of the O 3 pollution over YRD region.…”
Section: Introductionmentioning
confidence: 99%